The great American songbooks : musical texts, modernism, and the value of popular culture - Graham, T. Austin (Modernist literature & culture., 2013)
'The Great American Songbooks' shows how popular music shapes and permeates a host of modernism's hallmark texts. Austin Graham begins his study of 20th-century texts with a discussion of American popular music and literature in the 19th century.